2016
DOI: 10.1016/j.ctim.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Dancer perceptions of the cognitive, social, emotional, and physical benefits of modern styles of partnered dancing

Abstract: Objective To study dancers’ perceptions of the physical, cognitive, affective, and social benefits of partnered dancing. Method 225 dancers (71% female) were recruited through a community ballroom dance center and completed an online survey designed to measure their perceptions of the physical, cognitive, affective, and social benefits of modern, partnered dance styles (swing, Lindy Hop, and ballroom dancing). Subgroups were formed for analyses. For one set of analyses, groups based on length of dance partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
(27 reference statements)
3
28
0
6
Order By: Relevance
“…A much discussed effect of dance is its power to increase well‐being, quality of life, and mood . However, in keeping with the framework outlined above, we propose that well‐being is a secondary effect of deeper biological effects caused by the functions of dance just as has been suggested for music (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…A much discussed effect of dance is its power to increase well‐being, quality of life, and mood . However, in keeping with the framework outlined above, we propose that well‐being is a secondary effect of deeper biological effects caused by the functions of dance just as has been suggested for music (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…14,[20][21][22][23] Besides being a physical activity, dance also incorporates emotional, cognitive, and cultural aspects involving social interaction, sensory stimulation, motor coordination, and music. Some studies [24][25][26][27][28][29][30][31] use ''dance therapy'' (or ''dance intervention'') to refer to rhythmic and patterned body movements that are performed to music, while other authors define dance movement therapy as a process that improves one's emotional, social, cognitive, and physical integration. 20,32 Nevertheless, given their similarity, Koch et al 33 analyze both forms of treatment within the same review.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some findings promote dance as an innovative and successful treatment for stress and depression that may help maximize the effects of usual treatments. 20,[24][25][26][27][28][29][30][31][32][33] According to Toro,34 Biodanza is a ''human integration system of organic renewal, affective re-education, and of relearning of Life's original functions'' (p. 39). In contrast to dance and dance movement therapy, Biodanza involves leading ''vivencias'' through music, singing, movements, and group interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In individuals without PD, research has found that participation in partnered dance styles is associated with perceived cognitive, social, and emotional health benefits. 55 The combination of motor skill learning, Abbreviation: PEDro score, physiotherapy evidence database score. …”
Section: Non-motor Benefitsmentioning
confidence: 99%